Memories are Forever : Transhumanism and Cultural Memory in V for Vendetta, Oblivion and The Giver - Caetano, Joana Catarina de Sousa (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
A conceptual revolution has taken place in the 20th century, one that has radically altered ways of thinking about the Sciences, Philosophy, Linguistics and the Arts, giving birth to a new holistic worldview. The world has become a mutually interactive whole, with each part connected to every other part (K. Hayles, in Wolfe). However, the efforts made to combine these disciplines seem to address the future rather than the past, which is very often forgotten or ignored. Since the 1980s, more than becoming an essential part of daily life, technology – the concrete manifestation of human obsession with the Future – has penetrated the human body in such a manner that it has redefined the concept of Humanity, forcing us to reexamine the boundaries between humanity and technology, organic and mechanical, authentic and artificial. By resorting to conceptual tools borrowed from Posthumanism and Transhumanism Studies, I will try to understand whether, in a world driven by the persistent need to develop, update, upgrade and relentlessly move forward, there is still a place for cultural memory. Through the analysis of the presence/absence of memory in several Sci-Fi films, namely V for Vendetta (2005), Oblivion (2013) and The Giver (2014), which dwell on the subject of human improvement by scientific methods, I will set myself to acknowledge the relevance of cultural memory in human evolution.